Reproductive health data and its relationship to baseline brain imaging and cognitive measurements in cognitively unimpaired female PSEN1 E280A mutation carriers and non‐carriers from the API ADAD Trial. (20th December 2022) - Ghisays, Valentina; Vila‐Castelar, Clara; Giraldo‐Chica, Margarita; Acosta‐Baena, Natalia; Protas, Hillary D.; Malek‐Ahmadi, Michael H.; Chen, Yinghua; Luo, Ji; Lee, Wendy; Bocanegra, Yamile; Muñoz, Claudia; Herrera, Karina; et al.
Abstract: Background: The impact of sex steroid hormones on Alzheimer's disease (AD) remains to be further clarified. Research suggests that shorter reproductive span, late menarcheal age, early menopause, oophorectomies and hysterectomies, are associated with increased dementia risk. We examined reproductive health and its associations with brain imaging and cognitive measurements in unimpaired female Presenilin 1 ( PSEN1 ) E280A mutation carriers and non‐carriers from the Alzheimer's Prevention Initiative Autosomal Dominant AD (API ADAD) Trial (NCT01998841). Method: A total of 151 cognitively unimpaired 30‐53 year‐old females (101 PSEN1 mutation carriers and 50 non‐carriers) were included. Reproductive health data (i.e., menarcheal age, number of pregnancies, deliveries, miscarriages, and living children) from all participants were examined, as well as the extent to which menarcheal age was related to age‐adjusted baseline 1) cortical amyloid plaque burden (florbetapir PET), 2) Precuneus cerebral glucose metabolism (fluorodeoxyglucose PET), 3) hippocampal volume (3TMRI), and 4) the API ADAD preclinical cognitive composite score, which includes the MMSE Orientation score, CERAD Word List Delayed Recall and Constructional Praxis, Multilingual Naming Test and Raven's Progressive Matrices subset. We examined associations with the cognitive and brain imaging measures corrected for multiple comparisons (Bonferroni). Result: Carrier and non‐carrier females did not differ on number of pregnancies, deliveries, miscarriages, or living children. Female carriers had a significantly younger menarcheal age than non‐carriers (12.8 ±1.5 versus 13.7±1.6 years, p = 0.007, Bonferroni). Among carrier females, older menarcheal age was associated with lower scores on the Raven's test (Bonferroni: r = ‒0.28, p =0.035). Menarcheal age was not associated with scores on the cognitive composite or other individual subtests, or with brain imaging measures. Conclusion: Our findings suggest reproductive health data did not differ between carrier and non‐carrier females, except for a slightly younger menarcheal age compared to non‐carriers, and that menarcheal age may have a very limited impact on brain pathology and function at preclinical stages of ADAD. Longitudinal studies with larger samples are needed to clarify the extent to which earlier menarcheal age may be related to changes in cognitive function in mutation carrier females transitioning from preclinical to clinical stages.